Estimation of physical development of young sportsmen from traditional and modern positions - Khor'yakov V.A (Kharkov National Pedagogical University, 2012)
The problem of evaluation of anthropometric status of young sportsmen is examined with the use of method of indexes and modern pictures of somatic health of man. In research young boxers took part 10-11 (n=41), 12-13 (n=48) and 14-16 years (n=39). Contradiction and ambiguousness of estimations of physical development of children and teenagers is rotined by means of traditional indexes of Erismana, Quetelet, Pin'e, sthenic and development of thorax. It is marked that an estimation of physical development of children and teenagers with the use of standard deviation of selection is not productive, because in most cases distributing of the studied signs falls short of a normal law. A concept «norm» is recommended to replace a concept «norm» as an obligatory requirement of the state to the level of somatic health of children and teenagers of different regions of country. It is marked that it is expedient to examine physical development of individuals as a structural element of bodily condition the major components of which are indexes of power and capacity of mechanisms of energy supply.